Árboles de clasificación para el análisis de gráficos de control multivariantes - Gámez Martínez, Matías (2009)
In statistical quality control, one of the most widely used tools are the control charts. The main problem of the multivariate control charts lies in that they only indicate that a change in the process has happened, but they do not show which variable or variables are the source of this change. In the specialized literature thereare many approaches to tackle this problem, although the most usual consists on the decomposition of the T2 statistic. In this research, we propose an alternative method through the application of classification trees. The results show that this method constitutes a good tool to help to interpret the multivariate control charts.